Recycling of polyethylene via hydrothermal carbonization for the Li-ion battery anode - Hong, Soonhyun; Ku, Jahun; Park, Sunhye; Park, Jungjin; Yu, Young-Sang; Kim, Chunjoong (한국탄소학회, 2024)
Because plastics are cheap and light, their use is indispensable in our daily lives. However, the extensive use of plastics causes the disposal issue. Among various disposal processes, plastic recycling is of great attention because of minimizing waste and harmful byproducts. Herein, we recycle the most popular thermoplastic materials, high-density and low-density polyethylene, producing the anode materials for the Li-ion batteries. The electrochemical properties of the as-recycled soft carbon are investigated to study the energy storage capability as the anode of Li-ion batteries. Our work demonstrates the soft carbon recycled from plastic wastes is a promising anode material.